INTERNATIONAL ROLE OF HISTORICAL AND CULTURAL HERITAGE OF UZBEKISTAN (Academicia Globe: Inderscience Research, 2022)
This article discusses the historical and cultural heritage of Uzbekistan in the international arena, the impact of tourism activities, government decisions taken in this regard.